Determinants of Farmers' Participation in the Agricultural Sector Support Project for the Adoption of Improved Technology in Traditional Poultry Farming: Evidence from Rural Togo - Mawussi Kossivi Soviadan; Anselm Anibueze Enete; Chukwuemeka Uzoma Okoye; Zaneta Kubik (Journal of Agriculture and Environment for International Development (JAEID), 2023)
The adoption of improved technologies in agriculture has been shown to improve incomes, reduce poverty and contribute to rural development in many developing nations. In Togo, the Agricultural Sector Support Project (PASA) assists smallholder farmers in the adoption of the Improved Technology in Traditional Poultry Farming (ITTPF) in rural areas as a means of increasing smallholder incomes, enhancing food security and reducing poverty. However, the adoption rate is currently below expectations, especially given the promise it holds not only from an economic perspective but also from a broad environmental sustainability viewpoint since poultry manure can be used as a necessary input in smallholder farms. In this study, we examine the factors associated with the participation of farmers in PASA for the adoption of ITTPF in Togo. Our analysis covers 400 smallholder households in the 23 districts of Togo and employs Logit model with Probit model as robustness check. We find different socio-economic constraints and enablers of participation in PASA. Particularly, level of education, household size, membership in cooperative societies, hatching rate of eggs, farm size, average annual sale of poultry and self-financing capacity were positively and significantly related to the participation of farmers in PASA. The findings are robust to alternative specifications such as Probit model. Based on the findings, we argue that participation in agricultural innovation and development programs depends on the information accessible to farmers. One medium to improve information access could be agricultural cooperatives and extension services since they provide informal education, training, and access to productive inputs for farming and marketing purposes. Our findings suggest the need for agricultural policies which promote farmer organizations such as agricultural cooperatives coupled with effective extension services to enable the adoption of improved agricultural technologies.
Keywords: Q1; 330; Traditional poultry farming; Improved technology; Determinants; Adoption; Agricultural cooperative membership; Togo; Adoption of Agricultural Technologies; Effective Extension Services